ASSESSMENT OF READINESS OF FARMERS AND MSMES FOR MEDICINAL PLANT-BASED BUSINESS DEVELOPMENT IN KABUPATEN ASAHAN - Adetia Azmi Tanjung; Windi Triana; Rudy Irwansyah; Rahmawani (CV. Radja Publika, 2026)
This study aims to assess the readiness of farmers and micro, small, and medium enterprises (MSMEs) for medicinal plant-based business development in Kabupaten Asahan, North Sumatra, Indonesia. A quantitative descriptive design was employed involving 150 respondents, consisting of 90 farmers and 60 MSME actors selected through purposive sampling. Data were collected using structured questionnaires, field observations, and brief interviews. Farmer readiness was measured through land availability, cultivation knowledge, production resources, post-harvest capability, market access, financing, and willingness to collaborate. MSME readiness was assessed through raw-material availability, production capability, technology adoption, product innovation, financial management, licensing, packaging, marketing, and partnership readiness. Data were analysed using frequencies, percentages, mean scores, standard deviations, and a readiness index. The results showed that farmers achieved an average readiness score of 3.47 with a readiness index of 69.4%, while MSMEs obtained an average score of 3.39 with a readiness index of 67.8%. The combined readiness index reached 68.6%, indicating that both groups were generally ready to support medicinal plant-based business development. Farmers demonstrated strong readiness in land availability, farming experience, crop diversification, and collaboration. MSMEs showed strong entrepreneurial motivation, basic processing capability, product innovation, and partnership interest. However, weaknesses remained in post-harvest handling, technology, financing, market access, licensing, product standardization, branding, and digital marketing.The study concludes that Kabupaten Asahan has a favourable foundation for medicinal plant-based business development. Nevertheless, sustainable development requires an integrated value-chain approach involving farmers, MSMEs, local government, universities, financial institutions, and private-sector partners.